Pengaruh Struktur Modal dan Likuiditas dalam Meningkatkan Profitabilitas pada PT Unilever Indonesia Tbk. Tahun 2019-2023 - Marbun, Patricia Yosephine Syahrani (Asosiasi Dosen Akuntansi Indonesia, 2025)
This test was organized to see in case there is an impact of capital structure and liquidity on the profitability of PT Unilever Indonesia. To prove this influence, this test makes use of quantitative test methods to produce more accurate data. The data source obtained secondarily comes from the 2019-2023 periodical report of PT Unilever Indonesia Tbk. To prove the existing hypothesis, this research uses descriptive statistic tests, multiple linear regression analysis, t-test, f-test, and determinant coefficients. Partially, the result of this test shows that there is no valid impact of Debt Equity to Ratio (DER) as an indicator of capital structure and Current Assets as an indicator of liquidity on entity gain as scaled by Return on Equity (ROE). This is because the test results carried out are greater than the threshold or standard, namely 0.05